Relatório de Estágio Profissional "A Digressão: um musical de Desenvolvimento Profissional" - Henrique Castro Silva (2019)
The Tour: a musical of Professional Development, is a document elaborated by an intern student of Physical Education, in the scope of a Practicum training, inserted in the second cycle of studies in Teaching of Physical Education in Basic and Secondary Education of the Faculty of Sports of the University of Porto, held at a school in the same district. This document was written in the form of metaforic writing, directing it to the participation of a Vocalist in a Musical Tour, which is divided into seven chapters. The first chapter, "The Digression", contextualizes the realization and content of this document. The second chapter, "The Vocalist", characterizes and explains the beginning teacher expectations before the professional internship. The third chapter, "The Tour Frame", presents the legal and institutional framework of the internship; the intern student's understanding of the school as an institution; the description of the school in which it occurs, the advising teacher, the cooperating teacher and the internship group. The fourth chapter, "The Orchestra", addresses the detailed characterization of the classes that have been assigned. The fifth chapter, "The Music", reveals the intern student conduct starting from his conception of teaching, to the extension of his performance in the context of teaching The sixth chapter, "Relationship with the public", presents his intervention in the school community and the developed activities. The seventh chapter, "Perceived Problems of Beginning Teachers", presents a research study about the problems of beginning teachers, as a way of understanding the training process on a general and individual way. And the eighth, and last chapter, is about the final summary, conclusion and bibliographic references of the presented document.KEYWORDS: